LCP / PEI composite material for film and preparation method of LCP / PEI composite material

Through the blending of LCP/PEI composite materials and liquid crystal ionomers (LCI) in twin screw extrusion equipment, the problems of high temperature and high anisotropy during processing of LCP film materials are solved, and low cost is achieved. High-strength and high temperature resistant film preparation, suitable for food packaging and high-frequency communication fields.

CN119119690APending Publication Date: 2024-12-13SHANGHAI PRET CHEM NEW MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411211951.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

During the processing process, the existing LCP film materials have high temperature, lower viscosity, difficult to maintain shape, and high anisotropy, and high price. The extrusion film forming process has small output and low pass rate, making it difficult to meet the market demand heat resistance and Mechanical performance requirements.

Method used

Using LCP/PEI composite materials, the liquid crystal ionomer (LCI) prepared by mixing in a high-speed mixer and then performing sufficient melting and kneading in a twin screw extruder, using PEI and solution polycondensation reaction similar to the LCP melting temperature as Compatible agent reduces processing temperature, reduces anisotropy, and improves the strength and temperature resistance of the film.

Benefits of technology

Stable extrusion and film formation at low processing temperatures are achieved, and LCP composite polyester film with low anisotropy and high strength is obtained, which overcomes the problems of high molding temperature and large anisotropy and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005020530090000031
    Figure BDA0005020530090000031
  • Figure BDA0005020530090000032
    Figure BDA0005020530090000032
  • Figure BDA0005020530090000041
    Figure BDA0005020530090000041
Patent Text Reader

Abstract

The invention discloses an LCP (liquid crystal polymer) / PEI (polyetherimide) composite material for a film and a preparation method of the LCP / PEI composite material. The composite material is obtained by blending LCP, PEI and a liquid crystal ionomer (LCI) compatilizer. The composite material contains the following components in parts by weight: (1) 93-98 parts of LCP; (2) 2 to 5 parts by weight of PEI; and (3) 0.5 to 2 parts by weight of an LCI compatilizer. The LCI compatilizer is synthesized through solution polycondensation by taking bisphenol fluorene, composite binary acyl chloride and 4-hydroxynaphthylazo sodium p-benzenesulfonate as reaction monomers. The LCI realizes in-situ enhancement and compatibilization of a blending system through interaction of ions, and the compatibility is improved. The obtained composite material can be used for preparing a thin film through extrusion film forming. The composite material has excellent film-forming property, and the prepared film has excellent mechanical strength, heat resistance and barrier property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an LCP / PEI composite material for preparing a film and a preparation method thereof, belonging to the technical field of composite materials. Background Art

[0002] Thermotropic liquid crystal polymer (LCP) is a high-performance polymer material, generally known for its high strength, high modulus, excellent melt processing properties, inherent flame retardancy, low water absorption, chemical corrosion resistance and good radiation resistance, as well as many uses at high temperatures.

[0003] It is well known from existing technology that LCP can be prepared into film products. LCP film has the characteristics of high strength, high gas barrier, high and low temperature resistance, etc., and can be used in the field of packaging materials. In addition, with the comprehensive promotion of 5G technology applications and the further increase in communication frequency, the LCP film material has a low dielectric constant at high frequency, low dielectric loss and stable characteristics, which makes it play an irreplaceable role in communication base stations and mobile terminals.

[0004] The molecular structure of LCP is a rigid chain segment, which is in a liquid crystal state in the molten state, has excellent fluidity, and the finished product has high strength and high rigidity, but it also has the defect of anisotropy; and the molding temperature is high, and after the beginning of melting, the viscosity drops rapidly, and it is difficult to maintain the shape after extrusion molding, which has high requirements for processing equipment and technology. In addition, there is also the problem of high price.

[0005] At present, there are still some problems in the LCP extrusion blow molding or stretch film forming process worldwide, such as low output and low qualified rate. From the perspective of market demand, it is necessary to maintain the excellent heat resistance, mechanical properties and dielectric properties of LCP, and to produce LCP polyester film products with low price and easy processing. Summary of the invention

[0006] The purpose of the present invention is to solve the above technical problems and provide a LCP (liquid crystal polymer) / PEI (polyetherimide) composite material for film and a preparation method thereof. In addition, the present invention also aims to conveniently extrude and form a film using such a material.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] A LCP / PEI composite material for a film, comprising the following components:

[0009] (1) 93-98 parts by weight of LCP;

[0010] (2) 2-5 parts by weight of PEI;

[0011] (3) 0.5-2 parts by weight of LCI compatibilizer.

[0012] The liquid crystal polymer has a melting peak temperature between 260°C and 300°C; and a melt viscosity between 10 and 80 Pa·s, preferably between 25 and 60 Pa·s.

[0013] The liquid crystal polymer is a liquid crystal polyester formed by using an aromatic compound as a raw material monomer. The liquid crystal polymer is a liquid crystal polyester formed by polymerizing an aromatic hydroxycarboxylic acid and at least one compound selected from a combination of an aromatic dicarboxylic acid and an aromatic diol.

[0014] Part or all of the aromatic hydroxycarboxylic acids, aromatic dicarboxylic acids, and aromatic diols may be polymerizable derivatives thereof. Examples of polymerizable derivatives of compounds having hydroxyl groups such as aromatic hydroxycarboxylic acids and aromatic diols include acylated products formed by acylation of hydroxyl groups and conversion of hydroxyl groups to acyloxy groups.

[0015] Furthermore, the liquid crystal polymer has repeating units represented by formula (1), formula (2) and formula (3): repeating unit (1), repeating unit (2) and repeating unit (3):

[0016] Formula (1): -O-Ar1-CO-

[0017] Formula (2): -CO-Ar2-CO-

[0018] Formula (3): -O-Ar3-O-

[0019] In the formula, Ar1, Ar2 and Ar3 each independently represent a phenylene group or a naphthylene group.

[0020] The repeating unit (1) is selected from the repeating units of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid; the repeating unit (2) is selected from the repeating units of terephthalic acid, isophthalic acid and 2,6-naphthalenedicarboxylic acid; the repeating unit (3) is selected from the repeating units of hydroquinone, 2,6-naphthalenediol and 4,4'-dihydroxybiphenyl. The content of the repeating unit (1) is 58-72 mol %; the content of the repeating unit (2) is 9-21 mol %; the content of the repeating unit (3) is 9-21 mol %. The ratio of the content of the repeating unit (2) to the content of the repeating unit (3) is 0.9 / 1-1 / 0.9. The content of the repeating unit (1) is usually 30 mol % or more, preferably 42-88 mol %, more preferably 58-72 mol %. The content of the repeating unit (2) is usually 30 mol % or less, preferably 6-30 mol %, more preferably 9-21 mol %. The content of repeating unit (3) is usually 30 mol% or less, preferably 6-30 mol%, more preferably 9-21 mol%. The ratio of the content of repeating unit (2) to the content of repeating unit (3) is usually 0.9 / 1-1 / 0.9, and is preferably the same.

[0021] The liquid crystal polymer contains at least one naphthylene-containing repeating unit, and the total content of the naphthylene-containing repeating units in the liquid crystal polymer is 30-40%.

[0022] The glass transition temperature (Tg) of the PEI resin is above 210°C; and the heat deformation temperature (HDT) thereof under a pressure of 1.8MP is above 180°C.

[0023] The LCI compatibilizer has the following general structural formula:

[0024]

[0025] The n is an integer of 6-10.

[0026] The LCI is synthesized by solution polycondensation using bisphenol fluorene (formula i), composite dibasic acid chloride (formula ii) and sodium 4-hydroxynaphthalene azobenzene sulfonate (formula iii) as reaction monomers.

[0027]

[0028] The reaction molar ratio of the monomers of formula i, formula ii and formula i is 1-4:1-4:0.5-2.5.

[0029] The reaction equation is:

[0030]

[0031] The synthesis method of LCI comprises the following steps:

[0032] Dissolve 1 to 4 molar fractions of the monomer of formula i in o-dichlorobenzene to prepare a 0.5 to 5 wt% solution I, 1 to 4 molar fractions of the monomer of formula ii in o-dichlorobenzene to prepare a 2 to 10 wt% solution II, and dissolve 0.5 to 2.5 molar fractions of the monomer of formula iii in ethanol to prepare a 2 to 11 wt% solution III. Stir the above three solutions separately until they are homogeneous, place I and II in a condensation reflux reaction device and stir evenly. Heat the oil bath to 80 to 100°C, add solution III after 1 to 3 hours, and then react for 6 to 10 hours, during which time, stir evenly and continuously add 1 to 8 molar fractions of pyridine. After the reaction is completed, the product is placed in methanol for recrystallization. After the recrystallized polymer is filtered, washed with methanol, and then placed in a 60 to 90°C oven to dry for 12 to 24 hours to obtain a powder product.

[0033] The LCP / PEI composite material for the above-mentioned film is prepared by the following method: (1) adding PEI, LCP and LCI into a high-speed mixer and mixing at room temperature for 3-5 minutes to obtain a mixture; (2) adding the mixture into a twin-screw extruder, performing sufficient melt mixing to obtain a blend melt, and after extrusion granulation, obtaining an in-situ composite polyester; the operating temperature of the extruder is: 230±5°C for zone 1, 240±5°C for zone 2, 260±5°C for zone 3, 275±5°C for zone 4, 285±5°C for zone 5, 290±5°C for zone 6 and 285±5°C for zone 7.

[0034] The liquid crystal polymer composite material can be prepared by a known extrusion blow molding or extrusion biaxial stretching molding method to obtain a liquid crystal polymer composite film.

[0035] The design idea of ​​the present invention is to meet the above performances and mainly develop an in-situ composite material for the defects of LCP. The composite material uses PEI with a melting temperature close to that of LCP, firstly uses a solution polycondensation reaction to prepare a liquid crystal ionomer (LCI) as a compatibilizer, then melt-blended it with LCP and PEI, and extruded and granulated it through a twin-screw extruder. The composite material can be used to prepare an LCP composite polyester film with low processing temperature and small anisotropy.

[0036] The liquid crystal polymer composite material obtained according to the present invention has a low processing temperature during extrusion film forming, which is easy to control, and the obtained film material has small anisotropy, good strength and high temperature resistance. The liquid crystal polymer composite material of the present invention overcomes the difficulty of processing the liquid crystal polymer material at high temperature during film forming, and improves the defects of large anisotropy of the film after forming and actual use. DETAILED DESCRIPTION

[0037] The present invention is further described below by way of examples and comparative examples. Without violating the spirit of the present invention, the present invention should not be limited to the contents specifically shown in the following examples.

[0038] Product performance test method:

[0039] The present invention uses a differential scanning calorimeter (DSC 8000, PerkinElmer, USA) to test the melting point (T m ), tested according to ASTM D3418. Melt viscosity (MV) was tested using a capillary rheometer (RH 2200, Malvern, UK) according to ASTM D3835. Intrinsic viscosity was tested using an Ubbelohde viscometer with a diameter of 0.7 to 0.8 mm according to (GB / T14191)--2008.

[0040] Synthesis of Liquid Crystal Polymers:

[0041] Embodiment 1:

[0042] First, p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, hydroquinone, terephthalic acid and acetic anhydride are reacted at a constant temperature of 120-130° C. for 1 hour, then the temperature is raised to 185-195° C. within 2 hours, and the temperature is further kept constant for 0.5-1 hour, and the acetylation reaction is completed; then the acetate obtained by the acetylation reaction is subjected to a melt polycondensation reaction with p-naphthalenedicarboxylic acid, and the polymerization temperature is raised to a predetermined temperature within 3 hours to allow the polymerization reaction to proceed continuously; then the temperature is kept constant to allow the reactants to become prepolymers with a certain molecular weight; when the torque of the stirrer rises to a predetermined level, nitrogen is immediately introduced to terminate the polymerization reaction; and the nitrogen pressure is increased to 2 kg / cm 2 , releasing a liquid crystal polymer prepolymer. The monomer ratio for preparing the above liquid crystal polymer is as follows: 32 mol% p-hydroxybenzoic acid, 32 mol% 6-hydroxy-2-naphthoic acid, 18 mol% hydroquinone, and 18 mol% terephthalic acid. The obtained prepolymer 1 is heated from 25°C to 105°C in 1 hour, and then kept warm for 10 minutes; then heated from 105°C to 240°C in 1 hour, and kept warm for 10 minutes. Then, it is heated from 240°C to 250°C in 2 hours, kept warm for 1 hour, solid phase polymerization is carried out, and further cooled to obtain LCP1 with a melting point of 283°C and a melt viscosity of 50 Pa·s.

[0043] Embodiment 2:

[0044] Except for changing the monomer ratio of the liquid crystal polymer to 32 mol % p-hydroxybenzoic acid, 26 mol % 6-hydroxy-2-naphthoic acid, 21 mol % hydroquinone, and 21 mol % terephthalic acid, the other steps are the same as Example 1. The melting point of the prepared liquid crystal polymer is 262° C. and the melt viscosity is 45 Pa·s, which is called LCP2.

[0045] Synthesis of Liquid Crystalline Ionomers:

[0046] Example 3

[0047] 0.002 mol of the monomer of formula i was dissolved in 50 mL of o-dichlorobenzene to prepare solution I, 0.002 mol of the monomer of formula ii was dissolved in 20 mL of o-dichlorobenzene to prepare solution II, and 0.0010 mol of the monomer of formula iii was dissolved in 10 mL of ethanol to prepare solution III. The above three solutions were stirred to homogeneity, and I and II were placed in a condensation reflux reaction device and stirred evenly. The oil bath was heated to 80°C, and solution III was added after 1 hour, followed by a reaction for 6 hours, during which time 0.003 mol of pyridine was continuously added. After the reaction was completed, the product was placed in methanol for recrystallization. After the recrystallized polymer was filtered, washed with methanol, and then placed in an oven at 80°C for 12 hours to obtain a powder product LCI-1. The melting point was tested to be 264°C, and the intrinsic viscosity was 0.28 g / dL.

[0048] Example 4

[0049] Except that 0.0013 mol of the monomer of formula iii was dissolved in 15 mL of ethanol to prepare solution III and 0.0035 mol of pyridine was added dropwise, the other operations were the same as those in Example 3 to prepare a powder product LCI-2. The melting point was 271° C. and the intrinsic viscosity was 0.31 g / dL.

[0050] The preparation method of the liquid crystal polymer composite material is as follows:

[0051] Examples 5-8 and Comparative Examples 1-2

[0052] (1) LCP, LCI and PEI (purchased from Sabic, Ultem 1000) are added to a high-speed mixer and mixed at room temperature for 3-5 minutes to obtain a mixture; the mixture is added to a twin-screw extruder and fully melt-kneaded to obtain a blend melt, and after extrusion granulation, an in-situ composite polyester is obtained; the operating temperature of the extruder is: 230±5°C for zone 1, 240±5°C for zone 2, 260±5°C for zone 3, 275±5°C for zone 4, 285±5°C for zone 5, 290±5°C for zone 6, and 285±5°C for zone 7.

[0053] The liquid crystal polymer composite material prepared above is prepared by a known extrusion blow molding or extrusion biaxial stretching molding method to obtain a liquid crystal polymer composite polyester film. The raw material ratios, film forming properties and film properties of Examples 5-8 and Comparative Examples 1-4 are shown in Table 1. The anisotropy of the film is confirmed by the tensile strength in the transverse and longitudinal directions of the film. If the values ​​of the two are close, the anisotropy is small.

[0054] As can be seen from the table, in Examples 5-8, LCP, LCI, and PEI with melt viscosity and melting temperature within a certain range can be used to stably extrude and form films, and the prepared films have high strength, low anisotropy, and similar transverse and longitudinal mechanical properties. In Comparative Examples 3-4, when the PEI content is low, LCI is not added and stable extrusion and film formation cannot be achieved. In Comparative Examples 1-2, the PEI content is continued to increase, and although a film can be obtained without using LCI, the anisotropy is large and the performance difference in the two directions is large.

[0055] Table 1 Composite material components and properties

[0056]

[0057] In the table, ○ represents that the film can be stably extruded and formed; × represents that the film cannot be stably extruded and formed.

[0058] The liquid crystal polymer composite material of the present invention can be extruded into films conveniently and stably, and the prepared film has the characteristics of high strength and small anisotropy, and is therefore suitable for food packaging or high-frequency communication fields.

Claims

1. A LCP / PEI composite material for film, characterized in that: It is composed of the following components: (1) 93-98 parts by weight of LCP; (2) 2-5 parts by weight of PEI; (3) 0.5-2 parts by weight of LCI compatibilizer.

2. The LCP / PEI composite material for film according to claim 1, characterized in that: The liquid crystal polymer has a melting peak temperature between 260° C. and 300° C.; and a melt viscosity between 10 and 80 Pa·s, preferably between 25 and 60 Pa·s.

3. The LCP / PEI composite material for film according to claim 1, characterized in that: The liquid crystal polymer is a liquid crystal polyester produced using an aromatic compound as a raw material monomer.

4. The LCP / PEI composite material for film according to claim 3, characterized in that: The liquid crystal polymer is a liquid crystal polyester formed by polymerizing an aromatic hydroxycarboxylic acid and at least one compound selected from a combination of an aromatic dicarboxylic acid and an aromatic diol.

5. A LCP / PEI composite material for film according to any one of claims 1 to 4, characterized in that: The liquid crystal polymer has repeating units represented by formula (1), formula (2) and formula (3): repeating unit (1), repeating unit (2) and repeating unit (3): Formula (1): -O-Ar1-CO- Formula (2): -CO-Ar2-CO- Formula (3): -O-Ar3-O- In the formula, Ar1, Ar2 and Ar3 each independently represent a phenylene group or a naphthylene group.

6. The LCP / PEI composite material for film according to claim 5, characterized in that: The repeating unit (1) is selected from the repeating units of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid; the repeating unit (2) is selected from the repeating units of terephthalic acid, isophthalic acid and 2,6-naphthalenedicarboxylic acid; the repeating unit (3) is selected from the repeating units of hydroquinone, 2,6-naphthalenediol and 4,4'-dihydroxybiphenyl.

7. The LCP / PEI composite material for film according to claim 5, characterized in that: The content of the repeating unit (1) is 58-72 mol %; the content of the repeating unit (2) is 9-21 mol %; and the content of the repeating unit (3) is 9-21 mol %.

8. The LCP / PEI composite material for film according to claim 5, characterized in that: The ratio of the content of the repeating unit (2) to the content of the repeating unit (3) is 0.9 / 1 to 1 / 0.

9.

9. A LCP / PEI composite material for film according to any one of claims 1 to 4, characterized in that: The liquid crystal polymer contains at least one repeating unit containing naphthylene groups; the total content of the repeating units containing naphthylene groups in the liquid crystal polymer is 30-40%.

10. The LCP / PEI composite material for film according to claim 1, characterized in that: The glass transition temperature (Tg) of the PEI resin is above 210°C; and the heat deformation temperature (HDT) thereof under a pressure of 1.8MP is above 180°C.

11. The LCP / PEI composite material for film according to claim 1, characterized in that: The LCI compatibilizer has the following general structural formula: The n is an integer of 6-10.

12. The LCP / PEI composite material for film according to claim 11, characterized in that: The LCI is synthesized by solution polycondensation using bisphenol fluorene (formula i), composite dibasic acid chloride (formula ii) and sodium 4-hydroxynaphthalene azobenzene sulfonate (formula iii) as reaction monomers. The reaction molar ratio of the monomers of formula i, formula ii and formula i is 1-4:1-4:0.5-2.

5.

13. The LCP / PEI composite material for film according to claim 11, characterized in that: The synthesis method of LCI comprises the following steps: 1-4 molar fractions of the monomer of formula i are dissolved in o-dichlorobenzene to prepare 0.5-5wt% solution I, 1-4 molar fractions of the monomer of formula ii are dissolved in o-dichlorobenzene to prepare 2-10wt% solution II, and 0.5-2.5 molar fractions of the monomer of formula iii are dissolved in ethanol to prepare 2-11wt% solution III. The above three solutions are stirred to homogeneity respectively, and I and II are placed in a condensation reflux reaction device and stirred evenly; the oil bath is heated to 80-100°C, and solution III is added after 1-3 hours, and then reacted for 6-10 hours, during which time, 1-8 molar fractions of pyridine are continuously added; after the reaction, the product is placed in methanol for recrystallization, and the recrystallized polymer is filtered, washed with methanol, and then placed in a 60-90°C oven for drying for 12-24 hours to obtain a powder product.

14. The method for preparing the LCP / PEI composite material for thin film according to any one of claims 1-4 and 6-13, characterized in that: The preparation method is as follows: (1) adding PEI, LCP and LCI into a high-speed mixer and mixing at room temperature for 3-5 minutes to obtain a mixture; (2) adding the mixture into a twin-screw extruder, performing sufficient melting and kneading to obtain a blend melt, and after extrusion and granulation, obtaining an in-situ composite polyester; the operating temperature of the extruder is: 230±5°C for zone 1, 240±5°C for zone 2, 260±5°C for zone 3, 275±5°C for zone 4, 285±5°C for zone 5, 290±5°C for zone 6 and 285±5°C for zone 7.

15. A liquid crystal polymer composite film, characterized in that: The LCP / PEI composite material is prepared by extrusion blow molding or extrusion biaxial stretching molding according to any one of claims 1-4 and 6-13.